Benefits of promoting scholarship among program directors: promoting scholarship among directors is a win-win-win for institutions, trainees, and directors - Brandt, Patrick D.; Robinson, Donita L. (Frontiers in Research Metrics and Analytics, 2024)
When the National Institutes of Health (NIH) budget doubled in the late 1990s, it led to a rise in the number of PhD-trained scientists and to increased NIH-funded programs to diversify the biomedical workforce. This trend has seen more PhD scientists take on leadership roles as program directors in academia. These program directors are often highly skilled in research design and data analysis, and they bring a scholarly approach to their administrative duties. Despite organizational challenges, promoting scholarship among program directors offers numerous benefits, including enhanced institutional reputation and better training outcomes. Herein we use examples from peer reviewed literature to illustrate how publications by program directors have influenced national policies and practices in biomedical training. Encouraging more academic institutions to support program director scholarship can yield significant returns for institutions, trainees, and the directors themselves.